Pengaruh Pajak Kendaraan Bermotor Dan Bea Balik Nama Kendaraan Bermotor Terhadap Pendapatan Asli Daerah Dengan Pajak Bahan Bakar Kendaraan Bermotor Sebagai Pemoderasi - Ferdiansyah Ferdiansyah (Universitas PGRI Madiun, 2020)
The existence of motorized vehicles has become a very vital part of the community. So that it affects the increase in revenue from Motorized Vehicle Tax, Motorized Vehicle Transfer Fee Duties, Motorized Vehicle Fuel Taxes and Local Original Revenues. This study aims to determine the relationship of contribution of Motorized Vehicle Tax, Motorized Vehicle Transfer Fee Duty, Motorized Vehicle Fuel Tax to the Revenue of West Java Province. This type of research is associative with quantitative methods using the method of multiple linear regression analysis. From the results of the study showed that the Regional Tax consisting of Motorized Vehicle Tax, Motorized Vehicle Transfer Fee Duty and Motorized Vehicle Fuel Tax partially had a positive and significant effect on the Local Revenue. With Motor Vehicle Fuel Tax as a moderating variable simultaneously obtained positive and significant results, which means that it strengthens the influence between Motor Vehicle Tax and Motor Vehicle Title Transfer Fees on Original Income in West Java ProvinceKeywords; Regional Taxes; Motorized Vehicle Tax; Motorized Vehicle Transfer Fee Fees; Motorized Vehicle Fuel Taxes; Local Revenue